Inventory of the eastern Bering Sea sponge fauna, geographic range extensions and description of Antho ridgwayi sp. nov. - Stone, Robert P.; Lehnert, Helmut; Hoff, Gerald R. (Zootaxa, 2019)
A total of 493 sponges were collected with a bottom trawl during annual groundfish stock assessment surveys in the eastern Bering Sea in 2013, 2015, and 2016 to build an inventory of species in this largely unexplored region. We report here principally on the demosponge fauna collected during those surveys because identifications of hexactinellids are incomplete. We identified 42 unique demosponge taxa from the collection including geographical range extensions for 30 species; seven are new records for the Pacific Ocean. The collection also included three species new to science; two have been previously described (Plicatellopsis borealis Lehnert & Stone 2017, Spongosorites beringensis Lehnert & Stone 2017) and Antho ridgwayi sp. nov. described here. The new species differed from all northern hemisphere congeners in the complements and sizes of spicules. We document that the region is more species rich than previously suspected, particularly the continental slope where the majority of hexactinellid sponges are located.